A comprehensive performance study of HTML5-enabled WebApps. (2017) - Li, Xianfeng; Bao, Zhiqiang
Web applications (WebApps) built on top of HTML standards have the advantage of cross-platform portability. However, the user experience in terms of both functionality and performance provided by current generation WebApps is not comparable to native apps running on iOS or Android. Despite significant functional extensions in the new HTML5 standard, the poor performance of WebApps has not been addressed. To promote the adoption of WebApps, it is important to study their performance comprehensively. In this paper, we take Google Chrome as the target browsing engine, and evaluate its performance with a set of popular web pages and WebApps. We make in-depth analysis on the major performance-contributing aspects in a browser engine. Our study exposes a number of interesting observations, from which we make reasonings and provide suggestions for the optimisation of browser engines, as well as guidelines for developing efficient web-based applications.